Dinamika Pedagang Kaki Lima Di Alun-Alun Kota Jember Di Tengah Persaingan Globalisasi: Peran UMKM Lokal Dalam Pertumbuhan Ekonomi Kota Jember - Mila Mufira; Elegi Nur Aisah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to uncover the challenges and dynamics faced by Street Vendors in the Jember City Square in the context of globalization. Through the analysis of the final theory of capitalism, it was found that street vendors in Jember experienced characteristics such as superficiality, weakening of affection, loss of history, and the presence of new technology that affected the way they operated. This study uses a qualitative approach with realist ethnographic methods, collecting data through in-depth interviews and field observations. The results of the study show that street vendors face economic instability due to unbalanced competition with large companies, negative social stigma, and less supportive government policies. To overcome this problem, the government is advised to provide special areas that are organized, clean, and environmentally friendly and provide training and improve facilities so that street vendors can compete more effectively. Proper support is expected to maintain the existence of street vendors as an important part of the local economy in the era of globalization that continues to grow.